Pembuatan Cangkang Kapsul Keras dari Glukomanan Biji Salak (Salacca zalacca) dengan Penambahan Enzim α-Amilase Buah Kelor - Tri Annisa Abdullah; Zakir Sabara; Ummu Kalsum (Journal of Scientech Research and Development, 2023)
The purpose of this study was to examine the results of the fabrication and disintegration time of hard capsule shells made from salak seed glucomannan with and without the inclusion of α-amylase moringa fruit enzymes. To determine the effect of time, temperature, and the optimal concentration on the production of rigid capsule shells from glucomannan from zalacca seeds. This study makes use of both independent and dependent variables. The data was examined using functional group analysis using an FTIR spectrophotometer, and the hemicellulose from the seeds of the salak fruit was converted to glucomannan with the addition of the moringa α-amylase enzyme. The viscosity of the glucomannan gel variations of zalacca seeds differed, with gels from glucomannan flour with concentrations of 8%, 9%, and 10% (w/v) having viscosity values of 32.5 cP, 2049.75 cP, and 8007, 89 cP, respectively. While glucomannan with the Moringa fruit α-amylase enzyme The viscosity value gradually lowered with the addition of Moringa fruit extract. It reduced at 300°C temperature variation of 11221.02 cP, 400°C temperature variation of 11097.14 cP, and 500°C temperature variation of 10754.37 cP. The viscosity value gradually decreased after the addition of the αamylase moringa fruit enzyme. The 10 minute mixing time variation yielded the greatest viscosity value, 10261.74 cP, while the 50 minute mixing time variation yielded the lowest, 8681.76 cP. Furthermore, physical specifications with the inclusion of the α-amylase enzyme in Moringa fruit produced capsule shells that were thinner in color and conformed to conventional capsule shells.